2013
DOI: 10.1142/s0192415x1350047x
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Induces Apoptosis in Oral Cancer Cells Through P38β Inhibition

Abstract: Oral cancer is a common malignancy associated with high morbidity and mortality. While p38 MAPK is reported to be involved in different cellular activities such as proliferation and differentiation, reports rarely define the roles of the individual members of the p38 MAPK family in cancer. We used two unique cell lines developed by our lab representing chemically induced oral cancer cells (T28) and non-tumor cells (N28) obtained from tissues surrounding the induced cancer as a model to screen out whether p38 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 61 publications
3
42
0
Order By: Relevance
“…The anti-tumor activity of thymoquinone in oral cancer might be attributed to the down-regulation of p38β MAPK [115]. Besides, in head and neck squamous cell carcinoma, thymoquinone induced apoptosis involving an increase in Bax expression and caspase-9 activation, and induced autophagy which depended on increasing levels of autophagic vacuoles and LC3-II proteins, the specific autophagy markers [116].…”
Section: Nigella Sativa and Thymoquinonementioning
confidence: 99%
“…The anti-tumor activity of thymoquinone in oral cancer might be attributed to the down-regulation of p38β MAPK [115]. Besides, in head and neck squamous cell carcinoma, thymoquinone induced apoptosis involving an increase in Bax expression and caspase-9 activation, and induced autophagy which depended on increasing levels of autophagic vacuoles and LC3-II proteins, the specific autophagy markers [116].…”
Section: Nigella Sativa and Thymoquinonementioning
confidence: 99%
“…Lang and collaborators [97] showed that thymoquinone interfered with polyp progression in ApcMin mice through induction of tumor-cell specific apoptosis and modulation of Wnt signaling through activation of GSK-3 β . Thymoquinone also induced apoptosis in oral cancer cells through P38 β inhibition [98]. Odeh and collaborators [99] described the encapsulation of thymoquinone into a liposome, which maintained stability and improved bioavailability, while it maintained anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Primary oral cancer cells T8, T28, and non‐tumor cell N28 used in this study was kindly provided by Dr. Da‐Tian Bau, Department of Medical Research, China Medical University Hospital, Taiwan. Cell lines representing chemically induced oral squamous cell carcinoma (T8, T28) in C57BL/6J Narl mice, as well as non‐tumor cells (N28) obtained from tissues surrounding the induced cancer (Abdelfadil et al, ). Arecoline in combination with 4‐NQO was used in the drinking water of the mice to induce cancer.…”
Section: Methodsmentioning
confidence: 99%